Efficacy and safety of glucose, glucose and polidocanol combination, liquid polidocanol and polidocanol foam in the treatment of reticular veins: A randomized study in rabbits - Lucio Filho, Carlos Eduardo Pinheiro [UNESP]; Bertanha, Matheus [UNESP]; Prata, Marcela Polachini [UNESP]; Carvalho, Lídia Raquel de [UNESP]; Jaldin, Rodrigo Gibin [UNESP]; Sobreira, Marcone Lima [UNESP]; Janzen, Jan [UNESP]; Yoshida, Winston Bonetti [UNESP] (SAGE Publications, 2021)
Objective: To compare the efficacy and safety of sclerosing agents injected in dorsal veins of rabbit ears. Methods: Sixty ears of 30 rabbits were randomly allocated in: 1% liquid polidocanol, 1% polidocanol foam, 0.2% polidocanol-glucose 70% solution, glucose 75% or 0.9% saline. Outcomes included efficacy (luminal occlusion), complications (phlebitis, neovascularization, ulceration at the puncture site, necrosis and local inflammation) and histology (sclerosis, recanalization vein and surrounding tissues inflammation, blood extravasation, recanalization, lymphangiogenesis, destruction of cartilage and neoangiogenesis). Results: Sclerosis was superior in Foam Group (76.9%), but also with 30.7% necrosis (p = 0.003), 46.15% ulceration (p = 0.003), and 69.2% local inflammation (p < 0.0001). Neovascularization were similar. Histology showed 38.5% phlebitis (p = 0.004) and necrosis (p = 0.03) in the foam group. Conclusions: Sclerosis with foam and liquid polidocanol were superior to the other groups, but specially polidocanol foam at the expense of greater frequency of adverse events.
Keywords: animal models; efficacy; safety; sclerosing solutions; sclerotherapy; Varicose veins